Distribution of Lithodes confundens Macpherson, 1988 (Decapoda, Anomura) along the Atlantic continental shelf of southern South America - Sotelano, María Paula (2013)
The two lithodids here reported are spatially segregated on most of the Atlantic continental shelf off southern South America.At the northern limit of their distribution, off the Province of Buenos Aires, both species Lithodes santolla and L. confundes co-occur in the same area. The presence of L. confundens at a latitude of ca. 38°S as revealed by the museum material, expands its geographical distribution to the northern limit of the Magellanic biogeographical province (Balech & Ehrlich, 2008). The presence of L. santolla at latitudes as far north as 36°S was previously known (Boschi, 2000) following the subantarctic waters that run along the shelf break and sink at the Brazil/Malvinas confluence (Acha et al., 2004). The occurrence of both species at these latitudes is interesting from the biogeographical point of view because this is the only area where they co-occur. Larval dispersal from southern waters is unlikely, since larvae are lecithotrophic with limited swimming ability and epibenthic, associated to complex substrates (Tapella et al., 2012). Distribution of these lithodids is possible by adult migration (Thatje et al., 2005) and, hence, a continuous occurrence along the continental shelf increasing in depth with decreasing latitude should be expected between 37°S and 45°S. However, the present records for both species indicate disjunct distributions (i) for L. santolla in three different areas: Beagle Channel/Staten Island, Golfo San Jorge and off the Province of Buenos Aires and (ii) for L. confundens at the eastern entrance of the Straits of Magellan and Burdwood Bank, and the Province of Buenos Aires. In order to assess the exact distribution of both L. santolla and L. confundens, more sampling effort is required into parts of the south-western Atlantic continental shelf, where fisheries do not operate and for which no or little distributional data are available. On the fishery grounds, an improved identification of the lithodids captured should enhance our understanding of the exact distribution boundaries of the species, and help to identify areas where both species co-occur.